A synthetic biology approach for the treatment of pollutants with microalgae - Webster, Luke J.; Villa-Gomez, Denys; Brown, Reuben; Clarke, William; Schenk, Peer M. (Frontiers in Bioengineering and Biotechnology, 2024)
The increase in global population and industrial development has led to a significant release of organic and inorganic pollutants into water streams, threatening human health and ecosystems. Microalgae, encompassing eukaryotic protists and prokaryotic cyanobacteria, have emerged as a sustainable and cost-effective solution for removing these pollutants and mitigating carbon emissions. Various microalgae species, such as C. vulgaris, P. tricornutum, N. oceanica, A. platensis, and C. reinhardtii, have demonstrated their ability to eliminate heavy metals, salinity, plastics, and pesticides. Synthetic biology holds the potential to enhance microalgae-based technologies by broadening the scope of treatment targets and improving pollutant removal rates. This review provides an overview of the recent advances in the synthetic biology of microalgae, focusing on genetic engineering tools to facilitate the removal of inorganic (heavy metals and salinity) and organic (pesticides and plastics) compounds. The development of these tools is crucial for enhancing pollutant removal mechanisms through gene expression manipulation, DNA introduction into cells, and the generation of mutants with altered phenotypes. Additionally, the review discusses the principles of synthetic biology tools, emphasizing the significance of genetic engineering in targeting specific metabolic pathways and creating phenotypic changes. It also explores the use of precise engineering tools, such as CRISPR/Cas9 and TALENs, to adapt genetic engineering to various microalgae species. The review concludes that there is much potential for synthetic biology based approaches for pollutant removal using microalgae, but there is a need for expansion of the tools involved, including the development of universal cloning toolkits for the efficient and rapid assembly of mutants and transgenic expression strains, and the need for adaptation of genetic engineering tools to a wider range of microalgae species.